Morning glory : a novel - Jio, Sarah (PLUME, Published by the Penguin Group, 2013)
Fleeing an East Coast life marred by tragedy, Ada Santorini takes up residence on houseboat number seven on Boat Street. She discovers a trunk left behind by Penny Wentworth, a young newlywed who lived on the boat half a century earlier. Ada longs to know her predecessor's fate, but little suspects that Penny's mysterious past and her own clouded future are destined to converge.